Biology 2 - Cabrido, Avelinda Ardez (Mandaluyong City : Books Atbp. Publishing Corp., 2017)
"Biology 2 is a sequel to Biology 1which gives basic introduction to the fundamental concepts about cell structure and function, organic molecules that constitute a typical cell and their role in metabolism, and process of energy transformation taking place within the cell and how the energy produced is utilized to power all of cell's chemical activities. This book covers for parts: organismal biology, genetics, evolution and origin of biodiversity and systematics based on evolutionary relationships."
Includes references.
English text.
Keywords: Biology